High-dose oral vitamin D in combination with photodynamic therapy can accelerate the clearance rate of basal cell carcinoma: A randomized clinical trial - Edward V. Maytin; Nathalie C. Zeitouni; Abigail Updyke; Jeffrey T. Negrey; Alan S. Shen; Lauren E. Heusinkveld; Judith A. Mack; Bo Hu; Sanjay Anand; Terence A. Maytin; Laura Giostra; Taylor Bullock; et al. (Photodiagnosis and Photodynamic Therapy, 2025)
Background: Combining Vitamin D (VD) with photodynamic therapy (PDT) increases the clearance of actinic keratosis, but whether this might also be true for basal cell carcinoma (BCC) was unknown. Patient and Methods: In an intra-patient, randomized clinical trial, 35 patients with multiple BCC received 3 sessions of PDT using 20 % ALA (4 hr incubation) and 417 nm light. PDT was preceded by randomized pretreatments with either oral VD (10,000 international units) or placebo. Tumor size was monitored at each visit using 3-D photogrammetry to measure changes in lesion volume and height between visits, at submillimeter accuracy. Tumors that failed to resolve were biopsied. Results: Amongst 122 BCC tumors, 70 % (superficial and nodular subtypes) cleared completely, whereas 30 % (mainly aggressive histological subtypes) were PDT-resistant. To ask whether VD can alter the trajectory of BCC tumor clearance, 49 tumors that were visible at all 5 study visits were evaluated using kinetic slope analysis. Using a 3D photogrammetric height threshold that allows stratification of tumors into two PDT response categories (likely responders versus non-responders), we demonstrated that a majority (65 %) of thin tumors were responsive to VD (showed enhanced rate of clearance), versus only 22 % of thick tumors responded to VD. Some thin BCCs with aggressive histologic subtypes also responded to VD + PDT. Conclusions: PDT can be used to treat relatively thin BCC, but the addition of oral high-dose VD makes PDT even more effective. Neoadjuvant VD combined with PDT is safe and can hasten the resolution of appropriately selected BCC tumors.